2011
DOI: 10.1029/2011gl046724
|View full text |Cite
|
Sign up to set email alerts
|

Artificial small-scale field-aligned irregularities in the high latitude F region of the ionosphere induced by an X-mode HF heater wave

Abstract: [1] The effects on the high-latitude F region of the ionosphere by X-mode powerful HF radio waves injected towards the magnetic zenith (MZ) are analysed. The experiments were conducted using the EISCAT/Heating facility and UHF radar at Tromsø, Norway, the CUTLASS (SuperDARN) radar and the EISCAT ionosonde (dynasonde). The results show that the X-mode HF pump wave, radiated into the magnetic zenith from the HF heater, can generate very strong small-scale artificial field aligned irregularities (AFAIs) in the F-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 15 publications
5
45
0
3
Order By: Relevance
“…Blagoveshchenskaya et al . [, ] reported EISCAT UHF radar observation of an increase up to 30% in electron density over a wide altitude range induced by an X mode pump wave with frequency f HF ≈ f x F 2 , where f x F 2 is the critical frequency of the extraordinary wave for F 2 region. Senior et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blagoveshchenskaya et al . [, ] reported EISCAT UHF radar observation of an increase up to 30% in electron density over a wide altitude range induced by an X mode pump wave with frequency f HF ≈ f x F 2 , where f x F 2 is the critical frequency of the extraordinary wave for F 2 region. Senior et al .…”
Section: Discussionmentioning
confidence: 99%
“…The enhancements in N e / N e 0 presented in Figure have similarities to that given by Blagoveshchenskaya et al . [, ], Senior et al . [], and Borisova et al .…”
Section: Discussionmentioning
confidence: 99%
“…The growing body of X‐mode experiments at the EISCAT (European Incoherent Scatter) Scientific Association HF heating facility with the use of various multi‐instrument diagnostics showed that extraordinary (X‐mode) powerful HF radio waves are capable of producing a strong modification of the high latitudinal ionospheric F region, including the generation of the artificial field‐aligned irregularities (FAIs) (Blagoveshchenskaya, Borisova, Yeoman, Rietveld, ; Blagoveshchenskaya, Borisova, Yeoman, Rietveld, Ivanova, et al, ; Blagoveshchenskaya et al, ), optical emissions at red (630 nm) and green (557.7 nm) lines (Blagoveshchenskaya et al, ), and various spectral components in the narrowband stimulated electromagnetic emission spectra (Blagoveshchenskaya et al, ). Considerable study has been given to the HF‐enhanced ion and plasma lines (HFILs and HFPLs) from the EISCAT UHF incoherent scatter radar spectra excited under X‐mode heating, which are the signatures of the ion acoustic (IA) and Langmuir (L) electrostatic waves (Blagoveshchenskaya et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent experimental data, obtained at the EISCAT (European Incoherent Scatter Scientific Association) HF heating facility, demonstrate that an X ‐polarized HF pump wave can also produce the artificial field‐aligned irregularities (FAI), HF‐enhanced ion, and plasma lines (HFIL and HFPL) in the EISCAT UHF radar spectra. The phenomena mentioned above were generated in the underdense ionosphere in the frequency band f x F 2 ≥ f H > f o F 2 for any heater frequencies in the range f H = 4–8 MHz, where O ‐mode effects cannot be excited at all [ Blagoveshchenskaya et al ., , ]. In addition, only for the higher heater frequencies ( f H > 6 MHz) can the HFIL and HFPL also be excited even in the overdense ionosphere, f H < f o F 2 [ Senior et al ., ].…”
Section: Introductionmentioning
confidence: 99%